Environmental fragility in the Sahel - Ghins, Léopold; Madurga Lopez, Ignacio M.; Yabe, Kazuma; Marley, Jonathan (Organization for Economic Cooperation and Development, 2022)
A companion to the OECD States of Fragility 2022 report, this paper analyses the drivers and effects of climate and environmental risks in the Sahel,focusing on increasing food insecurity, rapid urbanisation and intensified mining. It outlines options for improved policy responses by providers of development co-operation.